Enhancing the degree of phase separation in binary self-assembled monolayers composed of 10-amino-1-undecanethiol and 6-carboxy-1-mercaptanethiol on Au (111) by using fluoren-9-ylmetyl N-(11-mercaptoundecyl)carbamate - Phong, Pham Hong (Vietnam Journal of Chemistry, 2016)
The degree of phase separation of binary Self-Assembled Monolayers  (SAMs) composed of 10-amino-1-undecanethiol (AUT) and 6-carboxy-1-mercaptanethiol (MHA) on Au (111) prepared by two methods has been compared. The first preparation method used direct-coadsorption of AUT and MHA from the bulk solution to give the binary SAMs of (d-AUT-MHA). The second method utilized fluoren-9-ylmetyl-N(11-mecaptoundecyl)carbamate (FAUT) to form the initial phase separated binary SAMs of FAUT-MHA having higher degree of phase separation than SAMs of d-AUT-MHA. Fmoc residues removal from SAMs of FAUT-MHA resulted in the final binary SAMs of AUT-MHA.The results obtained in the study of the SAMs by cyclic voltammetry and scanning tunneling microscopy provided clear evidences for the enhancement of phase separation in the final binary SAMs of AUT-MHA. Keywords. Binary self-assembled monolayers, phase separation, Fmoc.